2013
DOI: 10.3762/bjoc.9.147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and spectroscopic properties of 4-amino-1,8-naphthalimide derivatives involving the carboxylic group: a new molecular probe for ZnO nanoparticles with unusual fluorescence features

Abstract: SummaryOf a series of 4-substituted 1,8-naphthalimides, fluorescent 4-(6-piperidinyl-1,3-dioxo-1H-benzo[de]isoquinolin-2(3H)-yl)benzoic acid (4) was found to be a sensitive molecular probe for ZnO nanoparticles. We investigated in detail one- and two-photon absorption properties of this fluorophore. In nonpolar solvents, the acid 4 absorbs at about 400 nm and fluoresces at 500 nm with a fluorescence lifetime of about 7 ns, similar to the ester 6 and typical of the lifetimes of other derivatives of this type. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
3
11
0
1
Order By: Relevance
“…Moreover, dendrimers with amino-1,8-naphthalimide molecules in their structures were proposed as tunable organic light-emitting diodes [62]. Bekere et al [63] evaluated the possibility of using 4substituted 1,8-naphthalimides as sensitive molecular probes for ZnO nanoparticles. In this case, the nature of the interaction and how the molecule was adsorbed onto the nanoparticle were not studied.…”
Section: Biological Effect Of Ann Cnps and Ann-cnp Towards Anabaena mentioning
confidence: 99%
“…Moreover, dendrimers with amino-1,8-naphthalimide molecules in their structures were proposed as tunable organic light-emitting diodes [62]. Bekere et al [63] evaluated the possibility of using 4substituted 1,8-naphthalimides as sensitive molecular probes for ZnO nanoparticles. In this case, the nature of the interaction and how the molecule was adsorbed onto the nanoparticle were not studied.…”
Section: Biological Effect Of Ann Cnps and Ann-cnp Towards Anabaena mentioning
confidence: 99%
“…1,8‐Naphthalimide derivatives have been reported to be used in a variety of applications due to their strong electroactivity, fluorescence and photostability . They have been used in many fields such as fluorescent sensors, switchers and electroluminescent material .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] 1,8-Naphthalimide derivatives have been reported to be used in a variety of applications due to their strong electroactivity, fluorescence and photostability. 31 They have been used in many fields such as fluorescent sensors, switchers and electroluminescent material. 32 They have also been used as fluorescent markers and molecular probes in biotechnology and as sensitive electro-optic materials in solar cells and organic field-effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that dyes based on rhodamine have poor photostability [41,49]. Fluorescent dyes based on 1,8-Naphthalimide with strong photostability, tunable photophysical properties as well as low cytotoxicity make them as an ideal alternative fluorescent dyes in biomedical application [50][51][52][53]. Therefore, the objective of this research was to use the excellent photophysical properties of naphthalimide dyes and biocompatibility of PCU simultaneously, and design and synthesis novel fluorescent polymeric biomaterials (PCU) based on naphthalimide dye and study their physical, mechanical and blood-compatibility.…”
mentioning
confidence: 99%